2010
DOI: 10.1007/s12072-010-9189-z
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of liver stiffness following resolution of acute flares of chronic hepatitis B

Abstract: BackgroundMeasuring liver stiffness is becoming more popular as a non-invasive tool for assessing liver fibrosis.AimTo assess the effect of severe hepatitis B flare on liver stiffness and determine factors that correlate with liver stiffness measurements.MethodsTwenty-nine patients with severe hepatitis B flare (ALT > 10 × upper limit of normal) were followed up for 1 year. Serial transient elastography was performed at the time of flare, 3–6, and 12 months after flare.ResultsAt the time of flare, the median l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 18 publications
(21 reference statements)
1
30
0
Order By: Relevance
“…It is well known that acute liver flares can increase the LSM which returns back to near normal by 6 months, and further decreases at 12 months. Studies have shown previously that differences in ALT can be associated with different LSM [20][21][22]. In our study, we aimed at decreasing the influence of ALT levels on FS measurements by excluding patients with ALT C 2ULN, making the results much more accurate.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that acute liver flares can increase the LSM which returns back to near normal by 6 months, and further decreases at 12 months. Studies have shown previously that differences in ALT can be associated with different LSM [20][21][22]. In our study, we aimed at decreasing the influence of ALT levels on FS measurements by excluding patients with ALT C 2ULN, making the results much more accurate.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in patients with acute flare, TE examinations should be delayed until ALT levels are stabilized. Regarding this issue, several studies have tried to investigate the optimal period (3 to 6 months) to restore of reliability of TE values in patients with acute flare 16,86,87…”
Section: Limitations and Failurementioning
confidence: 99%
“…First, the extent of histological necroinflammatory activity influences TE results, resulting in an overestimation of TE values that increases in parallel with the degree of necroinflammatory score [29,41,42,68,69,70,71,72,73,74]. Since even mild to moderate ALT elevation is associated with higher LS values, and may cause discrepancies between TE results and the actual underlying fibrosis, physicians should exercise caution in interpreting TE results.…”
Section: Limitations Of Te and Future Perspectivesmentioning
confidence: 99%